Amino acid delta13C analysis of hair proteins and bone collagen using liquid chromatography/isotope ratio mass spectrometry: paleodietary implications from intra-individual comparisons. - Raghavan, M; McCullagh, J; Lynnerup, N; Hedges, R (2010)
We report a novel method for the chromatographic separation and measurement of stable carbon isotope ratios (delta(13)C) of individual amino acids in hair proteins and bone collagen using the LC-IsoLink system, which interfaces liquid chromatography (LC) with isotope ratio mass spectrometry (IRMS). This paper provides baseline separation of 15 and 13 of the 18 amino acids in bone collagen and hair proteins, respectively. We also describe an approach to analysing small hair samples for compound-specific analysis of segmental hair sections. The LC/IRMS method is applied in a historical context by the delta(13)C analysis of hair proteins and bone collagen recovered from six individuals from Uummannaq in Greenland. The analysis of hair and bone amino acids from the same individual, compared for the first time in this study, is of importance in palaeodietary reconstruction. If hair proteins can be used as a proxy for bone collagen at the amino acid level, this validates compound-specific isotope studies using hair as a model for palaeodietary reconstruction. Our results suggest that a small offset observed in the bulk delta(13)C values of the hair and bone samples may be attributed to two factors: (i) amino acid compositional differences between hair and bone proteins, and (ii) differential turnover rates of the tissues and the amino acid pools contributing to their synthesis. This application proposes that hair may be a useful complementary or alternative source of compound-specific paleodietary information.